Projeto e operação de cubas eletrolíticas para a indústria de alumínio - Zangiacomi, Carlos Eduardo (Universidade Federal de São Carlos, 2006)
The Brazilian aluminum industry is ranked among the sixth biggest aluminum producers worldwide and plays an important role in the local market. Continuous improvement in aluminum industry points to more metal output at lower costs. The potlining is an important subsystem in this process due to high cost involved and more recently due to environmental aspects. Using a systemic approach, this work aimed to increase potlife and thus minimize the aluminum costs. In this opportunity, a careful post-mortem analysis in electrolyte cells were performed to account for the sequence of incidents that led to the final pot failure and make the right decision to minimize or even eliminate the limiting factors to obtain a longer potlife. Besides pot failure mechanisms and pot design changes, some other factors that may be detrimental to potlife at Alcoa Aluminum S.A Pocos de Caldas, MG were also investigated thoroughly, such as preheating and pot start-up technique and lining materials (cathode bottom blocks technical and economic aspects). The results from this study were paramount to make the right decision in respect to pot design through minimizing pot design misconceptions and using appropriate materials. Both preheating and pot start-up procedure were also changed in an attempt to minimize the risks of fatal cathode damage caused by high thermal gradients during these two practices. Knowing that a perfectly constructed and operated cell is not easily obtained, all modifications in respect to pot design, lining material, preheating and pot start-up practices were based on solid and careful diagnosis and will certainly contribute to obtain a long potlife at Alcoa Aluminum Pocos de Caldas, MG.
Keywords: Alumínio; Revestimento cerâmico; Células eletrolíticas; Aluminum; Potlining; Electrolyte cell; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA